Perfil clínico-epidemiológico de crianças com alterações no desenvolvimento e filhas de mães usuárias de drogas na gestação - Programa Caminhar/Hospital Universitário Bettina Ferro de Souza - CARVALHO NETO, Américo Peixoto de (2022)
The main goal of this research was to identify and draw a clinical-epidemiologic profile of children with infantile developmental disability whose mothers were drug users during the pregnancy. These women were enrolled in Caminhar Program – Bettina Ferro de Souza University Hospital. This was a descriptive, explanatory and transversal work, in which 651 dossiers (100%) were reviewed from October 2002 to September 2005. 12 of these dossiers (1.84%) reported drug use during pregnancy. The average age of the children was 3.5 years; 75% of them were adopted. Alcoholic drink was the main overused drug. Prematureness, kernicterius and low birth weight were the most common alterations in newborn babies. The enlargement of basal cisterns, mega cistern magna and the damage of the pyramidal motor ways were detected. The meaningful clinical inter-occurrences correspond to motor delay, sleep disturbs, alterations of talk and respiratory infections. In conclusion, the drug used during the pregnancy works as a delaying factor in fetus formation and infantile development, causing severe disturbs that could be avoided with early identification, treatment and attendance of theses mothers who were drug users.